Change of civil neighborhood in the Spanish plurilegislative system: ¿Dónde queda la voluntad testamentaria? - Egusquiza Balmaseda, M.ª Ángeles (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
The civil neighborhood has been the central axis of the resolution of interregional conflicts in Spain. The civil law applicable to the succession “mortis causa” of the Spanish national has been made to depend on it. The qualification of civil neighborhood as a rule of conflict, of exclusive jurisdiction of the State - art. 149.1.8 CE-, has kept open a debate, now classic, that is important for the Spanish civil plurilegislative system. In particular, we warn about the rules of art. 9.8 of the CC, a rule that shows the lack of neutrality and parity in the mobile succession conflict when the different civil rights that coexist in Spain come into play. The reflection on the adaptation to the social reality of the current conflict regulations of the Civil Code, the effective scope of the testamentary will and the demanded legal renewal in this matter are the lees on which this work is based.